Computational Analysis for Characterization and Evaluation of Pentatricopeptide Repeat-Containing Protein (PPR) in Arabidopsis thaliana - Saidi, Abbas; Hajibarat, Zahra (Polish Journal of Natural Sciences, 2023)
Pentatricopeptide repeat (PPR) proteins are a great group of RNA-binding proteins which critical role plays in different range of biological stages. However, further investigation is necessary for deeper insight to their roles. Here, a total of 41 sequences of PPR genes were identified and characterized in Arabidopsis. A comprehensive analysis of PPR gene was performed containing chromosomal distribution, phylogenetic relationships, conserved motifs, and detection of transcription factor binding sites (TFBs). Analysis of TFBs illustrated that several transcription factors binding sites (TFBs) namely MYB, bZIP, WRKY, Homeodomain, and AP2 act as basic TFBs linked to abiotic stress responses as well as different growth stages. Our findings revealed a positive correlation between PPR promoter regions of genes and other genes. Expression analysis revealed that PCMP-H52 is induced under iron deficiency and shift low to high light stresses. PCMP-H52 was highly up-regulated in senescence stage in Arabidopsis. Our results can provide a comprehensive insight into the expression analysis of PPRs and their roles in optimizing biological structure and representing varied roles in PPR genes.